2021
DOI: 10.1370/afm.2672
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Expectations for Antibiotics in Patients With Upper Respiratory Tract Infections: A Primary Care Randomized Controlled Trial

Abstract: PURPOSE Many family practitioners prescribe antibiotics for patients with upper respiratory tract infections (URTIs) to meet patients' expectations. We evaluated the impact of providing brief tablet-based information about antibiotic treatment of URTIs on patients' expectations for antibiotics and on family practitioners' antibiotic-prescribing behavior.METHODS We performed a 3-arm randomized controlled trial among patients presenting with URTIs at 2 urban family practices in Auckland, New Zealand, during wint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Previous research has shown that it is feasible to change patients' expectations for antibiotics for URIs. 29 Additionally, communicating these findings to providers may empower them to assess and address patients' expectations by implementing successful interventions like communications training. [30][31][32] Patient satisfaction with URI visits has been shown to be a If Veterans answered at least one item within a subscale, they were included; however, some Veterans did not answer any items within a specific subscale and therefore the total N used in calculating means scores differed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that it is feasible to change patients' expectations for antibiotics for URIs. 29 Additionally, communicating these findings to providers may empower them to assess and address patients' expectations by implementing successful interventions like communications training. [30][31][32] Patient satisfaction with URI visits has been shown to be a If Veterans answered at least one item within a subscale, they were included; however, some Veterans did not answer any items within a specific subscale and therefore the total N used in calculating means scores differed.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately for Māori in NZ, there is both under-prescribing of necessary treatments and over-prescribing of inappropriate medications [ 21 ], creating and sustaining health inequities [ 4 , 5 ]. There is potential for ‘good prescribing’ when patients and their prescribers discuss the reasons for the medicine, including risks and benefits [ 1 , 17 , 18 ]. Our findings suggest a need to address the relationship between health providers and Māori ‘10,21].…”
Section: Discussionmentioning
confidence: 99%
“…The interview process consisted of a 20- to 40-minute discussion using a semi-structured guide ( Supplementary File S2 ) developed by the research team based on their research experience and on the published literature [ 16 , 17 ]. The investigator team reviewed the interview guide and pilot tested the wording of the questions for clarity and flow.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have identified the importance of good clinician-patient communication in reducing inappropriate use of antibiotics (8,9). Patients often do not expect antibiotics for acute RTI, but instead seek reassurance and information on what to expect (10,11,12). Similarly, physicians often face uncertainty about the natural course of RTIs, and who is more likely to experience complications (13).…”
Section: Introductionmentioning
confidence: 99%